A Study on Barriers Faced by School Heads in the Implementation of Inclusive Education in Sindh, Pakistan - Ali Gul Bugti1, Nadir Hussain (JIE, 2023)
Several research studies have already been conducted since the inception of the Salamanca Declaration in 1994 till to this time. It has been found on the basis of available literature that implementation of inclusive education is still a challenge for different under-developed and developedcountries of the world. Keeping this in view, it is essential to find out the barriers faced by the school heads in the implementation of inclusiveeducation in Sindh, Pakistan. T